Design and fabricate antitheft lock for motorcycle - Wan Mohd Hazwan, Wan Ariff (2008)
Using from the stolen motorcycle problem because did not have more lock security for motorcycle that’s really give high protection, a high protection security lock for motorcycle was design and build up. For make sure this product really high protection security antitheft lock, this product was developed after research another lock at the market. This product has two system of lock. First is for the rod as a main lock for this product. This rod will be lock at rim tire to make sure it cannot move. Second is steel cable wire. This cable is a flexible lock system that can lock at anywhere example at another motorcycle or at mast. To make sure this product really strength, welding joint use it to joint each part. This product actually can make another alternative for customer motorcycle to protect their motorcycle from theft. This product actually obtains the objective although it not easy to bring anywhere.